1985
DOI: 10.1111/j.1365-2133.1985.tb02060.x
|View full text |Cite
|
Sign up to set email alerts
|

The number and distribution of benign pigmented moles (melanocytic naevi) in a healthy British population

Abstract: Total body mole counts have been performed on 432 normal healthy Caucasian subjects aged 4 days to 96 years (204 males and 228 females). The mean total body mole count in the first decade of life is three for females and two for males, rising rapidly in the second decade to a mean of 23 for females and 18 for males. In the third decade numbers are highest, with a mean of 33 for females and 22 for males. Thereafter, numbers of moles slowly drop until in the eighth decade they have fallen to levels similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
1
6

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(136 citation statements)
references
References 8 publications
12
117
1
6
Order By: Relevance
“…While two previous studies have touched on the subject of inter-observer agreement on clinical diagnosis of nevi (MacKie et al, 1985;Cooke, 1988) (Cooke, 1988). The three observers reviewed 200 clinical photographs of flat, tan nevi 2 to 4 mm in diameter and concurred on a diagnosis of melanocytic nevus in 89% of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…While two previous studies have touched on the subject of inter-observer agreement on clinical diagnosis of nevi (MacKie et al, 1985;Cooke, 1988) (Cooke, 1988). The three observers reviewed 200 clinical photographs of flat, tan nevi 2 to 4 mm in diameter and concurred on a diagnosis of melanocytic nevus in 89% of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Although some older reports suggested that they should be removed to prevent malignant change, acral nevi are present in as many as 4-9% of the population, 60 and melanomas are very rare in these sites. Histologically, acral nevi tend to be more cellular than most common nevi, and the nevus cells may be arranged in predominantly lentiginous rather than nested patterns in the epidermis.…”
Section: Nevi Of Acral Skinmentioning
confidence: 99%
“…In adults, there have been no formal studies looking at the difference in naevus phenotype in countries with different exposure patterns. Based on naevus count studies, there is no evidence of a relationship between mean numbers of naevi per individual and melanoma incidence in different countries: naevus-counting studies in healthy individuals in Australia (Nicholls, 1973), New Zealand (Cooke et al, 1985) and the USA have not shown major differences in mean naevus count from those carried out in the UK (MacKie et al, 1985) and Switzerland (Sigg and Peloni 1989). However, these studies have involved different examiners and different naevus-counting protocols, and the results are difficult to compare.…”
mentioning
confidence: 99%